2020
DOI: 10.1080/15592294.2020.1834919
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat and cocaine impact mitochondrial epigenetics: effects on DNA methylation

Abstract: Human immunodeficiency virus (HIV) infection and the psychostimulant drug cocaine are known to induce epigenetic changes in DNA methylation that are linked with the severity of viral replication and disease progression, which impair neuronal functions. Increasing evidence suggests that changes in DNA methylation and hydroxymethylation occur in mitochondrial DNA (mtDNA) and represent mitochondrial genome epigenetic modifications (mitoepigenetic modifications). These modifications likely regulate both mtDNA repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Global 5-mC and 5-hmC mtDNA content Global hypomethylation of mtDNA in fructose-fed rats as well as higher mtDNA content and transcription of several mtDNA genes [116] It has been reported that mtDNA methylation is modulated by exposure to particulate matter (PM 1 and PM 2.5 ), air benzene, traffic-derived elemental carbon [56,108,113], particle-containing welding fumes [120], endocrine disruptors [109], maternal smoking [112,118,129], chrome [117], arsenic [59] and iron [121], as well as to the pharmacological agent valproic acid [51], to the demethylating agents 5-azacytidine and vitamin C [70,122] and to HIV infection and cocaine [125]. Variations in mtDNA methylation patterns have also been associated with various endogenous metabolites, including thyroid hormones [119], homocysteine [114,126], betaine [110], glucose [79,80], L-carnitine [124], lipopolysaccharides [127] and mitochondrial-derived peptides [123].…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Global 5-mC and 5-hmC mtDNA content Global hypomethylation of mtDNA in fructose-fed rats as well as higher mtDNA content and transcription of several mtDNA genes [116] It has been reported that mtDNA methylation is modulated by exposure to particulate matter (PM 1 and PM 2.5 ), air benzene, traffic-derived elemental carbon [56,108,113], particle-containing welding fumes [120], endocrine disruptors [109], maternal smoking [112,118,129], chrome [117], arsenic [59] and iron [121], as well as to the pharmacological agent valproic acid [51], to the demethylating agents 5-azacytidine and vitamin C [70,122] and to HIV infection and cocaine [125]. Variations in mtDNA methylation patterns have also been associated with various endogenous metabolites, including thyroid hormones [119], homocysteine [114,126], betaine [110], glucose [79,80], L-carnitine [124], lipopolysaccharides [127] and mitochondrial-derived peptides [123].…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Piracetam, cocaine, METH and morphine were prepared in cell culture-grade distilled water to obtain working concentrations. To investigate the effects of cocaine, METH, morphine and piracetam, the cultured cells were divided into eight groups: (i) control cells exposed to media alone, (ii) piracetam (10 μM), (iii) cocaine (1 μM), (iv) piracetam and cocaine, (v) METH (10 μM), (vi) piracetam and METH, (vii) morphine (5 μM), and (viii) piracetam and morphine for 24 h. The doses used in this study were based from our previous published studies [36][37][38][39]. Cocaine (1 μM), METH (10 μM), morphine (5 μM) and piracetam (10 μM) did not show any toxicity at particular mentioned concentrations.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…It was observed that Tat remained near to the mitochondria [ 57 , 58 ], suggesting cellular distribution is related to organelle alterations. Accordingly, other findings revealed that Tat-exposed cells present mtDNA damage [ 20 , 59 ] and alteration in its methylation patterns [ 60 ], mitochondrial membrane potential reduction [ 23 ] changes in size and morphology of the organelle, fusion-fission triggering [ 24 ], increased mitochondrial ROS [ 61 , 62 ], mitophagy disruption [ 17 , 57 ], mitochondrial functions dysregulation [ 17 , 61 ] calcium homeostasis disturbance [ 61 , 63 , 64 ], and apoptosis activation [ 23 , 58 , 61 , 65 , 66 ].…”
Section: Tat and Mitochondriamentioning
confidence: 99%